Assessment of national tobacco control program (NTCP) initiative on tobacco cessation among transgenders in Puducherry – A quasi-experimental study - Logesh Sidhu; Suriya Kumar; Priyadharshini Ragavane; Priyanga Chandrasekaran; Senthil Murugappan (Journal of Family Medicine and Primary Care)
Aim: This study aims to evaluate the impact of the National Tobacco Control Program initiative on the attitudes toward tobacco use and tobacco dependency among transgender individuals in Puducherry. Materials and Methods: A Quasi-experimental design was used to examine the effectiveness of the intervention. The study involved 52 transgender individuals from the SCOHD organization in Puducherry. The intervention included two awareness sessions, the Distribution of IEC materials during each session, and recreational activities for the participants. Changes in attitude toward tobacco use were measured using the Intention to Quit Tobacco questionnaire, while tobacco dependency among participants was assessed using the Fagerstrom Nicotine Dependency Scale (FNDS). Measurements were taken at baseline and third month to track the evolution of attitudes and dependency. Results: The program resulted in significant shifts in attitude and nicotine dependency among transgender individuals. This program indicated a positive trend, with an increase in individuals progressing to the contemplation and preparation stages, suggesting a growing willingness to reduce or quit tobacco use. The Fagerstrom Nicotine Dependency Scale showed a decrease in nicotine dependency over three months. Conclusion: The NTCP awareness sessions and follow-ups had a noticeable impact on altering attitudes toward tobacco use and reducing nicotine dependency among transgender individuals in Puducherry.